The determinants of foreign direct investment in Malaysia / Muhammad Nazrin Mahdhar - Mahdhar, Muhammad Nazrin (2015)
Foreign Direct Investment (FDI) plays an important role as a catalyst to the development and economic growth of a country. In particular, developing countries rely heavily on FDI to stimulate their economy as they face lack of capital for their development process. FDI inflows of Malaysia started fluctuating from 1996 to 2013 and this high volatility of Malaysia FDI inflows drew the researcher attention to study the factors affecting FDI inflows in Malaysia. Multiple linear regressions model is applied to study the connection between explanatory variables (market size, economic growth, official real effective exchange rate and inflation rate) and explained variable (Malaysia FDI inflow). Empirical results show that market size, economic growth and inflation rate positively affect Malaysia FDI inflows. Last but not least, exchange rates failed to establish a significant relationship with Malaysia FDI inflows.